Egg enrichment with vitamin D: The Sunshine Eggs projects. Issue 3 (23rd June 2021) - Clark, Adam; Kuznesof, Sharron; Davies, Sarah; Waller, Anthony; Ritchie, Avril; Wilson, Simon; Harbord, Lance; Hill, Tom
Abstract: Vitamin D deficiency is a significant public health issue in the UK with almost one in five adults having poor vitamin D status and most people failing to meet the Reference Nutrient Intake of 10 µg/day. There is an urgent need to address poor population vitamin D status through the development of food‐based strategies. Eggs can be enriched with vitamin D through manipulating vitamin D content in hens' feed. The Sunshine Eggs project was launched in 2015 through Innovate UK funding and brought together Noble Foods Ltd, DSM Nutritional Products Ltd and Newcastle University. The research demonstrated that feeding flocks of commercial hens up to 75 µg of 25‐D/kg (25‐hydroxyvitamin D3 via Rovimix ® Hy‐D ® ) of feed for 6 weeks improved egg total vitamin D content by 40%. These results informed the reformulation of the UK's leading free‐range egg brand 'Happy Egg' in October 2018, offering vitamin D–enriched eggs to the consumer. This article outlines the aims of a second Innovate UK‐funded Sunshine Eggs 2 project, which seeks to maximise the commercial potential of vitamin D–enriched eggs through several objectives. These relate to understanding (1) how storage/cooking methods affect egg vitamin D content; (2) whether enriched egg consumption improves vitamin D status in a human intervention trial; (3) consumer attitudes towards enriched eggs; and (4) market research to identify commercial opportunities for enriched eggs. The project seeks to drive fundamental impact across academic, commercial and public health nutrition sectors, in helping to offer viable vitamin D–enriched foods for UK consumers.